Prognostic Significance of Incident Complete Left Bundle Branch Block Observed Over a 40-Year Period - Imanishi, Ryo; Seto, Shinji; Ichimaru, Shinichiro; Nakashima, Eiji; Yano, Katsusuke; Akahoshi, Masazumi (The American journal of cardiology, 2006)
This case-control study was designed to assess the incidence and mortality of complete left bundle branch block (LBBB). We investigated 17,361 subjects (6,663 men and 10,698 women) who underwent biennial health examinations, including electrocardiography and cardiothoracic ratio measurements from 1958 to 2002. A total of 110 incident LBBB cases (41 men and 69 women) were observed, and their basic characteristics were compared with those of 456 age- and gender-matched controls (156 men and 300 women). Also, the possible association between LBBB and all-cause and cause-specific mortality was examined using a Cox proportional hazard model adjusted for age, gender, and underlying disease. The average age at LBBB diagnosis was 69.6 ± 10.0 years in men and 68.3 ± 10.9 years in women, and the incidence of LBBB increased progressively with age. Also, underlying disease, hypertension, and ischemic heart disease were significantly associated with LBBB. The cardiothoracic ratio was significantly different at the diagnosis of LBBB between those with LBBB and controls. Electrocardiographic manifestations before LBBB diagnosis included a higher rate of left ventricular hypertrophy and ST-T abnormalities in patients with LBBB. On Cox analysis, LBBB did not predict for all-cause mortality, but it did predict for mortality from congestive heart failure. In conclusion, the mean patient age at LBBB diagnosis was relatively elderly, and the LBBB incidence increased progressively with advancing age. Hypertension, ischemic heart disease, left ventricular hypertrophy, ST-T abnormalities, and an increased cardiothoracic ratio were associated with LBBB. LBBB predicted for mortality from heart failure but not for all-cause mortality, independent of age, gender, and underlying disease.